PEMANFAATAN DAN PENGEMBANGAN LAGU ANAK-ANAK DALAM PEMBELAJARAN TEMATIK PADA PENDIDIKAN ANAK USIA DINI / TK - Sinaga, Syarul Syah (Harmonia: Journal of Arts Research and Education, 2010)
Learning activity in Kinder Garden (TK) has never get out of music activity, although in general only singing activity. As one of learning media form, the children songs can be exploited to teach a various development area, including in it development language ability. Language ability is related to the song lyric. Based on that, the research contains about the developing theme learning of kids songs in kindergarten. This research is done with qualitative research. While research location determined randomly. The data was collected by interview, questionnaire, observation, and documentation. The data analysis is done by developing case description, that the process is data reduction, data categorization, and interpretation of data (verification / withdrawal of conclusion). Base of the observation, we know that the teachers in both of kindergarten (TK) becoming research location used the children songs as learning media of Indonesian vocabulary. Children songs as learning media of Indonesian vocabulary was assumed beside can facilitate vocabulary learning, multiply words knowledge and enrich children Language expression, also can used as learning media that support message of learning material, so children as learner can understand the contain of material learning and make learning process become more pleasant. Sometimes teachers get difficulties in choosing the songs of theme learning that consist of eleven songs. The real difficulty was found when teacher try to create songs and their lyrics. They can not find easily some matching words to built a song that according to learning material. Others difficulties are to match the phrases with the song melody, to match the syllables of the words with song melody and song sentence. In other side, melody, teachers difficulty are inÃ‚Â  the problem of ability to determine high or lower tone, tone value, and writing of song notation. Base of the research result, we suggest that institutes related to the early childhood education can continue the theme learning by plan and develop the training for teachers. Kata kunci: pengembangan, pembelajaran tematik, anak usia dini